Scanning Mutagenesis of Mcm1: Residues Required for DNA Binding, DNA Bending, and Transcriptional Activation by a MADS-Box Protein - Acton, Thomas B. (American Society for Microbiology, 2000)
MCM1 is an essential gene in the yeast Saccharomyces cerevisiae and is a member of the MADS-box family of transcriptional regulatory factors. To understand the nature of the protein-DNA interactions of this class of proteins, we have made a series of alanine substitutions in the DNA-binding domain of Mcm1 and examined the effects of these mutations in vivo and in vitro. Our results indicate which residues of Mcm1 are important for viability, transcriptional activation, and DNA binding and bending. Substitution of residues in Mcm1 which are highly conserved among the MADS-box proteins are lethal to the cell and abolish DNA binding in vitro. These positions have almost identical interactions with DNA in both the serum response factor-DNA and α2-Mcm1-DNA crystal structures, suggesting that these residues make up a conserved core of protein-DNA interactions responsible for docking MADS-box proteins to DNA. Substitution of residues which are not as well conserved among members of the MADS-box family play important roles in contributing to the specificity of DNA binding. These results suggest a general model of how MADS-box proteins recognize and bind DNA. We also provide evidence that the N-terminal extension of Mcm1 may have considerable conformational freedom, possibly to allow binding to different DNA sites. Finally, we have identified two mutants at positions which are critical for Mcm1-mediated DNA bending that have a slow-growth phenotype. This finding is consistent with our earlier results, indicating that DNA bending may have a role in Mcm1 function in the cell.